A motivation-based typology for natural event attendees. Issue 1 (2nd January 2019) - Kruger, Martinette; Saayman, Melville; Hull, John
ABSTRACT: Little research has been undertaken on the push and pull motives of attendees who travel to witness the natural phenomenon of the Salute to the Sockeye Festival held in British Columbia, Canada, celebrating one of the largest salmon runs, a water-based natural event, in the world. While numerous studies have focused on the motives of visitors to other events as well as to nature-based destinations we identified the said motives of these attendees and segmented the markets according to their motives. The results confirmed that attendees to natural events have a variety of motives for their trip and that segmenting visitors based on their motivations is a useful market segmentation tool as it provides a definitive profile and understanding of different types of visitors and their viewing preferences. The findings furthermore challenge the results of existing research findings that tourists are motivated by the need to escape from their everyday environment. Rather, attendees travelling to witness natural events are motivated by the specialness of the event i.e. the natural phenomenon and their appreciation of it. The findings enabled us to provide strategic insights for marketing and managing the salmon run viewing experience and similar natural events, according to the preferences of specific market segments. These strategies may be used by event organisers to ensure repeat visits, a memorable viewing experience and a greater appreciation of the natural wonder.